Excepcional: processos de design, arquitetura contemporânea e edifícios de apartamentos na cidade de São Paulo - Fábio Abreu de Queiroz (2021)
This thesis analyzes a number of apartment buildings produced by specific development companies in São Paulo. Their projects are considered exemplary of exceptional architecture by presenting innovative design and spatial characteristics, when compared to those os conventional buildings. The hypothesis is that such projects originate from design processes witch differ from the practices commonly adopted in São Paulo’s real estate market, in terms of the relations among the main involved actors, their objectives and the influence of their interests. The aim of this research is to investigate the design processes of such buildings and to identify organizations which would be more favorable for exploring architecture’s potential in the production of living spaces that are more coherent with contemporary ways of living, in the context of real estate market. The idea of complex systems is used as a conceptual tool.